DISTRIBUSI KELEMBABAN UDARA DENGAN METODE PEMANAS 60, 70, 80, 90 WATT TERHADAP VARIASI KECEPATAN UDARA - Munadi, Munadi (ROTASI, 2006)
At this century, growth of cooler machine very go forward, Along with growth of technology and information, this time met many cooler machine / refrigerator which is used in materials process specially in course of and humidifikation of dehumidifikation. On the basis of the require to the existence of a research to analyse influence of variation speed of secretory air of FCU and heater burden variation of to air characteristic distrisbusi in cold storage and also the nature of wet air termal exist in cold storage. In this case research done conducted with test-drive use cooler machine installation air cooled chiller special design that is by adding heater element in cold storage with heater energy variation of and variation of speed of air go out from FCU. Of equipments of this test is expected by the happening of degradation of dampness of air, and how its distribution [at] system and also know the nature of wet air termal exist in cold storage. Result of which is obtained from this examination that is at a speed of air go out from FCU 0.45 with heater burden 60 watt on course I got by dampness of relative ( RH ) equal to 90.4 %, dry ball temperature ( Tbk ) equal to 23.56 Â° C, and dew point temperature ( Td ) equal to 21,228 Â° C.